Digital Entrepreneurship Training for Unemployed Youth: A Community-Based MSME Incubation Program (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Youth unemployment remains a pressing socio-economic challenge, particularly in regions where access to education, digital literacy, and entrepreneurial opportunities is limited. In Gombong Sub-district, Kebumen Regency, many young people face barriers to entering the formal labor market despite the rapid growth of Indonesia’s digital economy. This training program was designed to empower unemployed youth by strengthening their entrepreneurial capacity through integrated learning modules.This study aimed to evaluate the effectiveness of a structured empowerment program in enhancing entrepreneurial competencies among unemployed youth in Gombong Sub-district, Kebumen Regency. A total of 30 participants (aged 17–25; 18 males, 12 females) with no prior entrepreneurial experience were enrolled. The intervention consisted of four sequential modules: (1) financial bookkeeping, (2) local wisdom-based business ideation, (3) digital marketing, and (4) creative production using manual and Direct-to-Film (DTF) printing. Mixed-method evaluation tools included pretest-posttest surveys, simulation tasks, rubrics, and checklists. Statistical analysis was conducted using paired t-tests to measure learning gains. Significant improvements were observed across all modules. In financial literacy, the average score increased from 64.7 to 90.4, with 90% of participants meeting competency standards. Business ideation yielded 28 proposals, with an average feasibility score of 92.4/100. Digital marketing scores rose from 38.5 to 81.2 (p < 0.001), and 90% of participants created functional online business accounts. In the printing module, 25 designs met quality benchmarks (≥80% clarity and alignment), and posttest scores improved from 65 to 95. DTF printing was rated higher in efficiency and market appeal, while manual printing was preferred for affordability. The program demonstrated short-term effectiveness in building entrepreneurial capacity among rural youth. However, limitations include the absence of long-term follow-up, market validation, and post-training support. Future research should explore scalability, sustainability, and integration with digital tools and funding mechanisms to enhance impact. It is recommended that similar empowerment programs be scaled up with stronger institutional support, wider access to digital incubation platforms, and sustained mentoring to ensure long-term business sustainability and contribution to the local creative economy.